Kajian mitigasi longsor menggunakan aplikasi Geo5 Versi 2.0 Studi kasus : Ruas Jalan Silondou-Malala Km. 364 Kabupaten Toli-Toli Provinsis Sulawesi Tengah - Rahmat, Ian (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
A landslide disaster occurred on the Silondou-Malala km road. 364 Tolitoli Regency, Central Sulawesi Province. Therefore, it is necessary to study landslide disaster mitigation to reduce the impact of risk or as a quick and appropriate action in handling when a landslide disaster occurs. The initial stage of the landslide mitigation study is to make observations regarding the causes and types of landslides, the next step is to carry out a detailed geotechnical survey. After the results of the investigation are obtained, a slope stability analysis will be carried out using the Geo5 version 2.0 application. The method used is the finite element method. The aim of this research is how to study landslide disaster mitigation on the Silondou-Malala km.364 road section and how to determine the technical handling of landslides on the Silondou-Malala km.364 road section using the Geo5 version 2.0 program. The results of field investigations showed that the landslide occurred due to poor management of drainage and box culvert type crossing structures. The results of this research show that the mitigation study carried out was structural mitigation, where there were three forms of treatment carried out at the landslide location. The treatment is to drain surface water by creating a good drainage management system, controlling seepage water by creating conductive channels at the edge of the slope, and creating cantilever type retaining walls.